2015
DOI: 10.3892/or.2015.4358
|View full text |Cite
|
Sign up to set email alerts
|

Klotho inhibits human follicular thyroid cancer cell growth and promotes apoptosis through regulation of the expression of stanniocalcin-1

Abstract: Abstract.The new anti-aging gene Klotho has been identified as a multi-functional humoral factor which influences multiple biological processes, including tumor progression. Although ample evidence indicates that Klotho plays important roles in cervical, lung and breast cancer, the role and mechanism of Klotho in thyroid cancer are still unclear. The present study aimed to investigate the effects and mechanisms of Klotho in human thyroid cancer cell lines FTC133 and FTC238. Klotho overexpression markedly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Overexpression of Klotho inhibited the proliferation and induced apoptosis of T-cell lymphoma cells. The results are consistent with the studies in lung cancer (7,17). Moreover, it has been reported that soluble Klotho and conditioned medium from Klotho- overexpressing cells could suppress the growth of pancreatic cancer and breast cancer cells (16,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overexpression of Klotho inhibited the proliferation and induced apoptosis of T-cell lymphoma cells. The results are consistent with the studies in lung cancer (7,17). Moreover, it has been reported that soluble Klotho and conditioned medium from Klotho- overexpressing cells could suppress the growth of pancreatic cancer and breast cancer cells (16,26).…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating evidence has implicated that Klotho is extensively downregulated in several solid malignancies (6)(7)(8)(9). Klotho was revealed to modulate the activity of several signaling pathways, including the FGF signaling, insulin-like growth factor-1 receptor (IGF-1R) and Wnt pathways (5,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies employing RNA-Seq detect no or very little thyroid Klotho (a Fragments Per Kilobase Of Exon Per Million Fragments Mapped (FPKM) value of 1.93, which amounts to roughly 2 transcripts per cell) [52,55]. Follicular thyroid carcinoma cells express Klotho in vitro, and Klotho was suggested to inhibit cell proliferation and survival [98]. This observation is consistent with a tumour suppressor function of Klotho.…”
Section: Accepted Manuscriptmentioning
confidence: 73%
“…Some studies have suggested the anti-apoptosis effect of STC1, such as colorectal cancer [27, 28], breast cancer [19, 29], glioma tumor [11, 30], thyroid cancer [20, 31], ovarian cancer [32, 33] and so on. Others indicated the pro-apoptosis effects.…”
Section: Discussionmentioning
confidence: 99%